Perioperative experiences of anesthesia reported by children and parents. Issue 2 (21st December 2017) - Perrott, Claire; Lee, Clover‐Ann; Griffiths, Sian; Sury, Michael R. J.
Summary: Background: The Sprint National Anaesthesia Project reported feedback from adults but not from children. We developed questionnaires for children and parents, and conducted a survey of perioperative anesthetic experiences in a large pediatric hospital. Methods: Patients undergoing elective general anesthesia were selected randomly each weekday over 10 weeks. Parents and children were approached within 4 hours after awakening, and were asked to complete a short questionnaire. Personal or patient identifiable data were not collected. Questionnaires were processed by optical mark reading technology and descriptive data analysis was performed. Results: Seven hundred and forty parents and 250 children completed questionnaires. The most common symptoms reported by parents were thirst and hunger (76%), drowsiness (75%), sore throat (41%), and pain of the surgery (38%). Sixty‐four percent of children felt worried or scared about something before the procedure: common worries were about the "anesthetic, " "procedure, " or "needles/cannula." Fifty‐five percent reported postoperative pain. Thirty‐nine children (15.6%) remembered something between going to sleep and waking up although distress was not reported; of these, the most common experiences remembered included hearing voices (34%), feeling sore (20%), and being worried (14%). Twenty‐two parents (2.9%) had any complaint and most were about fasting instructions. Only 3 parents would not recommend the anesthetic service. Conclusion: This study shows that the experiences of children and their parents are similar to those of adults reported by the Sprint National Anaesthesia Project. Thirst (and hunger), anxiety, and pain continue to be common problems for many children. This feedback may help direct interventions and research to improve the pediatric patient and parent experience with anesthesia.